Mechanical and thermal properties of polyamide 6 nanocomposite toughened with epoxidised rural rubber-25 - Navid, Nematzadeh (Scientific.Net, 2011)
Polyamide (PA6) is an engineering plastic with wide range of applications and the development in the field of montmorillonite (MMT) filled polymer nanocomposites has resulted in the development of PA6/MMT nanocomposites. However, MMT filled PA6 nanocomposites are notch sensitive and brittle at low temperatures, which posed as a major setback for many of its applications. The main objective of this study is to enhance the toughness of PA6/MMT (100/4) nanocomposites with epoxidised natural rubber-25 (ENR25). The ENR-25 content in the composites ranged from 15 to 30 wt%. The PA6/ENR/MMT nanocomposites were extruded and injection molded into tensile and impact test samples. The addition of ENR25 into PA6/MMT nanocomposites improved the impact strength of the nanocomposites while tensile modulus and tensile strength decreased with increasing ENR25 content. The thermal properties of PA6/ENR/MMT nanocomposites were also investigated via thermal gravimetric analysis (TGA). Both T10% and derivative thermal analysis (DTA) determined the lower thermal stability of PA6/MMT nanocomposites after addition of ENR.